ChemInform Abstract: Ultrasound Assisted One‐Pot Synthesis of Benzo‐Fused Indole‐4, 9‐dinones from 1, 4‐Naphthoquinone and α‐Aminoacetals. Issue 37 (August 2016) - Luu, Quang H.; Guerra, Jorge D.; Castaneda, Cecilio M.; Martinez, Manuel A.; Saunders, Jong; Garcia, Benjamin A.; Gonzales, Brenda V.; Aidunuthula, Anushritha R.; Mito, Shizue
Abstract: The synthesis of benzo[f]indole‐4, 9‐diones in one‐pot from 1, 4‐naphthoquinone and α‐aminoacetals is reported.